Developing a treatment for hand‐clapping maintained by automatic reinforcement using sensory analysis, noncontingent reinforcement, and thinning. (4th October 2020) - Slocum, Sarah K.; Yatros, Nicolette; Scheithauer, Mindy
Abstract: Two subjects diagnosed with autism spectrum disorder and related disabilities who engaged in hand‐clapping maintained by automatic reinforcement participated in this study. We conducted a sensory analysis to evaluate matched stimuli that functioned as an abolishing operation or extinction for different sources of sensory reinforcement. Finally, we implemented noncontingent reinforcement (NCR) using the stimuli found to compete in the assessment to reduce the target behavior, and we thinned item availability. Results showed a decrease in hand‐clapping, and hand‐clapping remained low when we thinned the schedule of reinforcement. This research further elucidates how NCR can treat problem behavior maintained by automatic reinforcement.